Tryptophan supplementation modulates social behavior: A review. (May 2016) - Steenbergen, Laura; Jongkees, Bryant J.; Sellaro, Roberta; Colzato, Lorenza S.
Highlights: Tryptophan supplementation enhances serotonergic functioning. Prosocial behaviour relies on serotonergic functioning. Tryptophan promotes prosocial behaviour. Tryptophan improves control over antisocial behaviour. Abstract: Tryptophan (TRP), the precursor of serotonin (5-HT), is one of the most investigated amino-acids. TRP supplementation can increase 5-HT levels in the brain and for this reason numerous studies have investigated whether administration of TRP can positively influence social behavior that relies on serotonergic function. Here we review the available studies on TRP, to clarify if and under what circumstances TRP supplementation might modulate social behavior. TRP supplementation seems to improve control over social behavior in patients and individuals suffering from disorders or behaviors associated with dysfunctions in serotonergic functioning. In contrast, in healthy humans TRP supplementation seems to promote social behavior. Although more research is needed to disentangle and understand the relations between individual differences, TRP effectivity, 5-HT functioning, social interactions, and context, we conclude TRP can be a promising tool for modulating social behavior.